Normative Data for Email Writing by Native Speakers of British English - Lindsey Thiel; Karen Sage; Paul Conroy (Journal of Open Psychology Data, 2015)
This dataset includes emails from forty two control participants ranging from 16 to 88 years of age (mean = 46) and 9 to 24 years of education (mean = 13). Three emails were produced by each participant (between 2011 and 2014), each within a time limit of three minutes. It is expected that this normative data will be useful for clinicians and researchers working with adults with acquired language disorders in assessing email writing.